METAPHORICAL REPRESENTATION OF KNOWLEDGE STRUCTURES IN LITERARY TEXTS - Rakhmonova Farangiz Abdusattor qizi, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
In literature, metaphors serve as cognitive frameworks that interpret abstract concepts into concrete, understandable ideas. This article based on Conceptual Metaphor Theory, examines how metaphors function as philosophical, emotional, and cultural frameworks in works such as “The Great Gatsby” (the green light) and “Macbeth” (life as a "brief candle"). The study emphasizes the function of intertextual patterns (like gardens and journeys) and narrative-shaping metaphors (like cyclical time in García Márquez) in encoding meaning and directing interpretation. Ultimately, the article highlights that metaphorical representations in literature serve as powerful tools for communicating knowledge, shaping thought, and offering insights into the human experience.